Dampak Bangkitan Tarikan Pengembangan Kawasan Perkantoran Sigi Terhadap Kinerja Lalu Lintas pada Kawasan Bora - Bahar, Taslim; Ramlan, Ratnasari; Islam, Ahmad Muhammad Syaiful (Berkala Forum Studi Transportasi antar Perguruan Tinggi, 2024)
The Sigi Regency Government relocated office areas and built several new offices in the Bora District. This activity was carried out as a result of the natural disaster that occurred in Sigi Regency in 2018. This study aims to determine the impact of office development activities in Bora on traffic performance in the vicinity. The method used is the procedure in the Highway Capacity Manual Indonesian (MKJI) 1997 for roundabouts and unsignalized intersections, and it calculates the effects of drag and generation. The study results show that the traffic performance at the Bora roundabout and the existing conditions on all arms are included in the level of service category A. Likewise, at intersection 2, the existing conditions for all arms are included in the level of service category A. Generation and attraction impacts due to the opening of the office area for five years. The traffic performance at the Bora roundabout will be included in the level of service category A. Likewise, the traffic performance at intersection two is included in the level of service category A. ABSTRAK Pemerintah Kabupaten Sigi merelokasi daerah perkantoran dan membangun beberapa kantor baru di Kecamatan Bora. Kegiatan ini dilakukan sebagai dampak bencana alam yang terjadi di Kabupaten Sigi di tahun 2018. Penelitian ini bertujuan untuk mengetahui dampak kegiatan pengembangan perkantoran di Bora terhadap kinerja lalu lintas di sekitarnya. Metode yang digunakan adalah prosedur pada Manual Kapasitas Jalan Indonesia (MKJI) 1997 untuk bundaran dan simpang tak bersinyal serta menghitung dampak tarikan dan bangkitan. Hasil penelitian menunjukkan pada kinerja lalu lintas di bundaran Bora kondisi eksisting pada semua lengan termasuk dalam kategori tingkat pelayanan A. Demikian halnya pada persimpangan 2, kondisi eksisting untuk semua lengan termasuk dalam kategori tingkat pelayanan A. Dampak bangkitan dan tarikan akibat terbukanya kawasan perkantoran 5 tahun mendatang, kinerja lalu lintas di bundaran Bora termasuk dalam kategori tingkat pelayanan A. Demikian pula kinerja lalu lintas simpang 2, termasuk dalam kategori tingkat pelayanan A.